Adaptation and Change in Practices in Neuro-Intervention during COVID-19 Pandemic: Experience from Department of Interventional Neurology at Referral Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Infectious Diseases, 2022)
Background: Different adaptation and changes have been practiced during COVID-19 pandemic.Objective: In this paper we investigated the impact of the COVID-19 pandemic on service delivery in the department of interventional neurology and adaptation of the department to the changed environment.Methodology: This was a retrospective analysis of diagnostic digital subtraction angiography (DSA) procedures done from January 2018 to December 2020 and were analyzed to detect significant breaks in time trend.Results: A total of 358, 426 and 251 patients got admitted for DSA in consecutive three years from 2018 to 2020 respectively. There was a sudden drop in the number of DSA procedures from 30 to 50 patients per month in the pre-COVID era before March 2020 to less than 10 patients per month during the COVID period of March to June 2020. However, the situation gradually improved following the introduction of RT-PCR test for SARS CoV-2 in June 2020. A poison regression showed a significant increase in monthly DSA procedures in the year 2019 compared to the year 2018, but a significant decrease in the pandemic year of 2020.Conclusion: By incorporating COVID-19 testing as a pre-requisite test before DSA procedures, the department of interventional neurology recovered from experiencing a significant drop in the number of performed DSA procedures in the initial periods of the pandemic to reaching a level observed in the pre-COVID era.Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S3-S8